2021
DOI: 10.3389/fnagi.2021.744719
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Prevents Surgery-Induced Persistent Neural Inhibition and Cognitive Dysfunction

Abstract: Perioperative neurocognitive disorders (PND) encompass short-term delirium and long-term cognitive dysfunction. Aging increases the susceptibility to PND, yet the neural mechanism is not known. In this study, we monitored the dynamic changes of neuronal activity in the prelimbic cortex before and after surgery. We found that anesthesia combined with surgery, but not anesthesia alone, induced a prolonged decrease in neuronal activity during the post-operation period in the aged mice, but not in the adult mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…An EE means more room to move, more objects to explore, entertain, and exercise, and greater motor and sensory stimulation than a CE, which may help maintain cognitive stability or reduce cognitive impairment due to brain injury. 43,44 Similar to a previous report, 29 the present study found that EE improved cognitive impairments following acute sleep deprivation (Figure 1). Further experiments found that activation of basal forebrain PIEZO1 abrogated the cognitive protective effect of EE (Figure 2), suggesting that the basal forebrain and PIEZO1 signaling may be the possible brain regions and signaling mechanisms of EE-induced memory maintenance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An EE means more room to move, more objects to explore, entertain, and exercise, and greater motor and sensory stimulation than a CE, which may help maintain cognitive stability or reduce cognitive impairment due to brain injury. 43,44 Similar to a previous report, 29 the present study found that EE improved cognitive impairments following acute sleep deprivation (Figure 1). Further experiments found that activation of basal forebrain PIEZO1 abrogated the cognitive protective effect of EE (Figure 2), suggesting that the basal forebrain and PIEZO1 signaling may be the possible brain regions and signaling mechanisms of EE-induced memory maintenance.…”
Section: Discussionsupporting
confidence: 91%
“…Various pet toys, including small houses, seesaws, rainbow channels, swings, L‐shaped tunnels, crawling tubes, inclined ladders, fitness rings, and running wheels, were placed in clear acrylic cages (40 × 30 × 40 cm). They were changed each morning with new toys of different colors and shapes to stimulate learning and active exploration 29 . Five mice were housed per cage to ensure proper socialization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that hippocampal microglial cells activated by different stress could transform their morphology and increase their motility to activate a series of inflammatory signaling pathways, leading to the upregulation of proinflammatory cytokines in the hippocampus ( Karve et al, 2016 ; Yang et al, 2021 ). Moreover, upregulated inflammatory cytokines in the hippocampus are closely related to depression and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…NOR test is commonly employed to study learning and memory in rodents [ 36 ], as previously reported [ 37 ]. During the habituation phase, the rats were placed in the center of a chamber (90 × 90 × 60 cm) without objects and allowed to explore the chamber for 10 min.…”
Section: Methodsmentioning
confidence: 99%